1997
DOI: 10.1021/bi971106i
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman, Infrared, and EPR Investigation on the Binuclear Site Structure of the Heme-Copper Ubiquinol Oxidases from Acetobacter aceti:  Effect of the Heme Peripheral Formyl Group Substitution

Abstract: Acetobacter aceti produces two different terminal ubiquinol oxidases (cytochromes a1 and o) depending on the culture conditions. Two types of oxidases share a common protein moiety but with different heme components at the binuclear center (heme A for cytochrome a1 and heme O for cytochrome o). We investigated the structure of the binuclear site of the two oxidases using resonance Raman, Fourier transform-infrared (FT-IR), and EPR spectroscopies to clarify the interactions of heme A formyl group with protein m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 62 publications
2
12
0
Order By: Relevance
“…The clear difference in the peak positions of the major bound azide band between bovine cytochrome c oxidase (2051 cm −1 ) and the ubiquinol oxidases (2041 cm −1 ) suggests such distinctions. Indeed, a similar difference was previously observed for the bridging cyanide stretching vibrations (2152 versus 2146 cm −1 , respectively) [7,11,13] and was explained due to the difference in the Cu B ‐N‐C bond angle and Cu B ‐N bond distance [14].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The clear difference in the peak positions of the major bound azide band between bovine cytochrome c oxidase (2051 cm −1 ) and the ubiquinol oxidases (2041 cm −1 ) suggests such distinctions. Indeed, a similar difference was previously observed for the bridging cyanide stretching vibrations (2152 versus 2146 cm −1 , respectively) [7,11,13] and was explained due to the difference in the Cu B ‐N‐C bond angle and Cu B ‐N bond distance [14].…”
Section: Discussionsupporting
confidence: 80%
“…Substitutions with asymmetrically 15 N‐labelled azides ( 15 N 14 N 14 N and 15 N 15 N 14 N), however, did not cause a splitting of the infrared band. Further, we found that a major bound azide band at 2041 cm −1 of the Acetobacter aceti ubiquinol oxidase did not cause a splitting upon the 15 N isotope substitutions for both ba ‐ and bo ‐type enzymes in the air‐oxidized state [11]. These properties are very similar to the corresponding band at 2051 cm −1 of the azide‐inhibited air‐oxidized bovine cytochrome c oxidase [4,8].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…However, a time-dependent change subsequently occurs in the Raman spectrum, involving a slow shift in frequency of the formyl stretching mode of heme a 3 , from 1,660 to 1,667 cm Ϫ1 . Immediately after reduction, the frequency of the a 3 formyl stretching mode (1,660 cm Ϫ1 ) observed in this enzyme is the lowest among the heme a 3 -containing oxidases, where this mode occurs in the 1,662 to 1,669 cm Ϫ1 range (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). The absence of spectral changes in the other modes, including the oxidation state marker, 4 , at 1,355 cm Ϫ1 (data not shown), indicates that the oxidation, coordination, and spin states are not changing as a function of time after reduction in either of the hemes.…”
mentioning
confidence: 86%
“…The interesting recognition phenomena are the binding of dioxygen in the binuclear reaction center and the transfer of electrons and protons to O 2 (Yamazaki et al, 1999). The binuclear reaction center has been extensively characterized also by FTIR using CO, NO, CN À and N 3 À as spectroscopic probes (Tsubaki et al, 1996(Tsubaki et al, , 1997Zhao et al, 1994). Depending on the redox state of the different redox centers within the bovine heart cytochrome c oxidase, the stretch frequency of the CO ligand is observed between 1959 and 1965 cm À1 (Yoshikawa et al, 1977;Yoshikawa and Caughey, 1982).…”
Section: Recognition Phenomena Recognition Phenomena In Heme Proteinsmentioning
confidence: 99%